2019
DOI: 10.1039/c9fo00386j
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of milk fat globule membrane (MFGM) proteins from donkey colostrum and mature milk

Abstract: The composition and functions of milk fat globule membrane (MFGM) proteins are important indicators of the nutritional quality of milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…It has been indicated to be more suitable for children and elderly people due to its remarkable nutritional value and less allergenic. Besides, milk fat globules in DM are smaller and more easily digested and absorbed by infants ( 2 ). With its obvious advantages, the demand of direct consumption for DM has increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been indicated to be more suitable for children and elderly people due to its remarkable nutritional value and less allergenic. Besides, milk fat globules in DM are smaller and more easily digested and absorbed by infants ( 2 ). With its obvious advantages, the demand of direct consumption for DM has increased.…”
Section: Introductionmentioning
confidence: 99%
“…To reveal the differences in the formation of MFGM in different mammals, the MFGM proteins of cow, yak, buffalo, goat, horse, camel and human were also compared by iTRAQ proteomics ( 6 ). Recently, Li et al hoped to explore the changes in the regulation mechanism of different lactation stages by analyzing the differences of MFGM proteins between donkey colostrum and mature milk ( 2 ). However, studies of the DM MFGM proteome are relatively sparse and less comprehensive, especially fully comparative analyses of MFGM protein compositions and potential biological activities between DM and other species.…”
Section: Introductionmentioning
confidence: 99%
“…Milk fat globule membrane (MFGM) secreted from the apical membrane carries a part of the cytoplasmic fraction of MECs, and they also represent partial information on the proteome of terminally differentiated MECs 23 . Studies on MFGM proteome reported a total of 632, 137, 947 and 1104 proteins in cattle, goat, donkey, and human respectively 24,25 . On the other hand, a proteomics study on mice mammary tissue suggested the biological significance of RNA polymerase B transcription factor 3 (BTF3) in the differentiation of MECs during pregnancy 26 .…”
Section: Discussionmentioning
confidence: 99%
“…This important information helped identify the main proteins with immunity-promoting properties for newborns [66]. These analyses have been performed to study and compare the proteome of various MFGMs, mainly from humans and cows [64][65][66], but also from other species such as the goat, yak, buffalo, horse, and donkey [61,62,[67][68][69][70].…”
Section: Comparison Of Mfgm Proteome Between Different Species and Lamentioning
confidence: 99%
“…These analyses have been performed to study and compare the proteome of various MFGMs, mainly from humans and cows [ 64 , 65 , 66 ], but also from other species such as the goat, yak, buffalo, horse, and donkey [ 61 , 62 , 67 , 68 , 69 , 70 ].…”
Section: Comparison Of Mfgm Proteome Between Different Species Andmentioning
confidence: 99%